Comparative Genome Analyses Highlight Transposon-Mediated Genome Expansion and the Evolutionary Architecture of 3D Genomic Folding in Cotton. (11th May 2021) - Wang, Maojun; Li, Jianying; Wang, Pengcheng; Liu, Fang; Liu, Zhenping; Zhao, Guannan; Xu, Zhongping; Pei, Liuling; Grover, Corrinne E; Wendel, Jonathan F; Wang, Kunbo; Zhang, Xianlong
Abstract: Transposable element (TE) amplification has been recognized as a driving force mediating genome size expansion and evolution, but the consequences for shaping 3D genomic architecture remains largely unknown in plants. Here, we report reference-grade genome assemblies for three species of cotton ranging 3-fold in genome size, namely Gossypium rotundifolium (K2 ), G. arboreum (A2 ), and G. raimondii (D5 ), using Oxford Nanopore Technologies. Comparative genome analyses document the details of lineage-specific TE amplification contributing to the large genome size differences (K2, 2.44 Gb; A2, 1.62 Gb; D5, 750.19 Mb) and indicate relatively conserved gene content and synteny relationships among genomes. We found that approximately 17% of syntenic genes exhibit chromatin status change between active ("A") and inactive ("B") compartments, and TE amplification was associated with the increase of the proportion of A compartment in gene regions (∼7, 000 genes) in K2 and A2 relative to D5 . Only 42% of topologically associating domain (TAD) boundaries were conserved among the three genomes. Our data implicate recent amplification of TEs following the formation of lineage-specific TAD boundaries. This study sheds light on the role of transposon-mediated genome expansion in the evolution of higher-order chromatin structure in plants.